Isothermes und thermisch-mechanisches Ermüdungsverhalten von Verbundwerkstoffen mit Durchdringungsgefüge (Preform-MMCs) - Ulrich, Oliver (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2013)
This study deals with the fatigue behaviour of metal-matrix-composites (MMCs) having ceramic contents of 30 to 39 Vol-%. The MMCs where produced by way of infiltrating a ceramic preform by an aluminium alloy. The characterisation of the MMC's cyclic and fatigue behaviour was researched on the basis of isothermal and thermal-mechanical fatigue tests.